KAJIAN PEMBERDAYAAN MASYARAKAT DENGAN PENDEKATAN STRUCTURAL EQUATION MODEL DI SEKITAR SUAKA MARGASATWA PALIYAN - , EKO PRANOTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
objective The high dependence of local communities on Paliyan Wildlife Reserve is a major problem in the management area. The of this study is: (1) determine and analyze the factors that affect the level of empowerment of peasent land in Paliyan Wildlife Reserve, (2) determine and analyze the factors that affect the level of participation of peasent land in Paliyan Wildlife Reserve, ( 3 ) to formulate an effective strategy efforts to increase the empowerment and participation of peasent land community development programs around the Paliyan Wildlife Reserve. Sites is the Paliyan Wildlife Reserve and surrounding villages namely Karangduwet, Karangasem, Jetis and Kepek Gunung Kidul Regency , Yogyakarta Special Region. Data collection was conducted in April 2013 to July 2013 . The study design was a survey, and research studies are explanations ( explanatory survey ) which describes causal relationship between the study variables through hypothesis testing . Sampling was done in stages (multistage random sampling). Collection of secondary data and primary data using questionnaires, interviews and observations of the 165 respondents. Processing and analysis of data using descriptive and inferential statistics. Inferential statistical analysis using Structural Equation Model (SEM) AMOS program. The results showed that the level of empowerment and participation of smallholder farmers in Paliyan Wildlife Reserve being classified in the category with the average score of 59 to level the score 57 for the empowerment and participation levels. SEM analysis showed that the factors that predominantly affect the level of empowerment of smallholder farmers is the opportunity or opportunities, the process of counseling and social environmental characteristics. While the level of participation of smallholder farmers directly affected by the level of factor empowerment, opportunity or opportunities, social and environmental characteristics of individual characteristics. Effective strategies and efforts to increase the participation of smallholder empowerment to community development programs around the area is Paliyan Wildlife Reserve (1) the increase in the chance/ opportunity so that farmers can be more empowered and able to participate, (2) increasing the empowerment and participation of farmers through the support of social environmental characteristics, (3) increasing the role of forestry extension in increasing farmers' empowerment and participation.